Accountability Practices in Pacalang: An Ethnomethodological Study - Suryantari, Eka Putri; Wiagustini, Ni Luh Putu; Sudana, I Putu; Rasmini, Ni Ketut (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Aside from its main duty as a security unit in a banjar (a traditional Balinese neighborhood), a pacalang carries out an additional task. The pacalang also plays an active role in collecting contributions for land management in the neighborhoods of the city of Denpasar. In connection with this additional task, the pacalang practices financial accountability. The question in this research is how does a pacalang understand accountability in relation to the implementation of this task. As a traditional organization at the neighborhood level, the pacalang is oriented towards maintaining security and public order in its area, but they have an additional task of collecting financial contributions. The aim of this research is to reveal and explore the deeper meaning in the understanding and practice of accountability on the part of the pacalang. This research was conducted using an ethnomethodological approach; the data were collected by conducting interviews, observations, and compiling documentation. Research data analysis was carried out using the Garfinkel approach. This research has resulted in the results of the meaning and interpretation of accountability practices, especially financial accountability that is carried out by a person who is in charge of a pacalang unit. The main implication of this research that more task to the pacalang, the more financial accountability will be applied on top of the other types of accountability implications and the contribution of this study is that it provides richness to the most recent theory of accountability practices within an ethnic group.